ANALYSIS OF STUDENTS' PROBLEM IN WRITING ARGUMENTATIVE TEXTS - Mei Maria Meliana Situmorang; Elisabeth Hutabarat; Yesinta Panjaitan; Yenita Sembiring (Universitas Muhammadiyah Tangerang, 2020)
AbstractWriting is a unique ability that only some people might have. but it is unexpected that everyone also has the same ability to write something. Neither by arguing, although all can submit opinions or ideas about something, many of them are not able or not know how to argue properly and correctly. Aware of this, the author tries to find the constraints and problems experienced by the research subjects when they want to argue, especially through the text of the argumentation. Found that there were problems encountered when writing the argumentation text, it turns out that the obstacles experienced by the subject during the process of writing the argumentation text are very diverse, ranging from reasoning about something to lack of motivation to dare to argue. With the existence of this study we as authors and researchers hope that this research can be a reference for subsequent research and not only limited to that, the hope of the authors of this study can be a reference to the problems experienced by students’j in writing argumentative text.